2016
DOI: 10.1016/j.joca.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Acid ceramidase treatment enhances the outcome of autologous chondrocyte implantation in a rat osteochondral defect model

Abstract: Objective The overall aim of this study was to evaluate how supplementation of chondrocyte media with recombinant acid ceramidase (rhAC) influenced cartilage repair in a rat osteochondral defect model. Methods Primary chondrocytes were grown as monolayers in polystyrene culture dishes with and without rhAC (added once at the time of cell plating) for 7 days, and then seeded onto Bio-Gide® collagen scaffolds and grown for an additional 3 days. The scaffolds were then introduced into osteochondroal defects cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Addition of rhAC to the culture media could correct this phenotype, further indicating the bioactivity of the enzyme and the fact that it can be taken up by this important cell type. We and others have shown that there is an important and unique relationship between sphingolipids and cartilage integrity [32] , [33] , and in the future it will be interesting to examine this further in the context of Farber disease.…”
Section: Discussionmentioning
confidence: 90%
“…Addition of rhAC to the culture media could correct this phenotype, further indicating the bioactivity of the enzyme and the fact that it can be taken up by this important cell type. We and others have shown that there is an important and unique relationship between sphingolipids and cartilage integrity [32] , [33] , and in the future it will be interesting to examine this further in the context of Farber disease.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to Farber disease, the therapeutic potential of recombinant AC also has been investigated in other diseases where ceramide pathology has been demonstrated, for example to reduce inflammation/infection in Cystic Fibrosis and to assist in cartilage repair after joint injury ( Pewzner-Jung et al, 2014 ; Xia et al, 2015 ; Frohbergh et al, 2016 ; He et al, 2017 ; Becker et al, 2018 ). In the current work we have focused on investigating the potential protective effects of recombinant AC on hepatic IR injury, and further understanding the underlying mechanism(s) contributing to these effects.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have also demonstrated a positive effect of ACDase in chondrocyte differentiation. In cartilage replacement therapy, pre-treatment with ACDase induces chondrocyte proliferation, the production of glycosaminoglycan, the expression of COL2 , the adhesion of chondrocytes to a scaffold, a reduced resorption after implantation, and an improved differentiation to cartilage [ 116 ]. Furthermore, a variation of FRBRL characterized by peripheral osteolysis not associated with MMP-2 and MMP-14 was found, suggesting the involvement of ASAH1 in bone remodeling [ 117 ].…”
Section: Role Of Ceramidases In Tissue Regeneration and Healingmentioning
confidence: 99%